"I Can Help Them Become Better Teachers, But I Can't Help Them With Educative Teacher Performance Assessment": Cooperating Teachers' Knowledge and Experience of the Educative Teacher Performance Assessment in Physical and Health Education. Issue 4 (August 2022) - Parkes, Craig; Holden, Shelley L.; O'Leary, Nick; Brunsdon, Jamie
Utilizing a thematic analysis approach, this case study investigated cooperating teachers' (CTs) knowledge and experience of the educative Teacher Performance Assessment (edTPA) in physical and health education. Participants were 14 certified physical education (PE) and/or health education CTs from a single school district in Alabama. Data were collected through one-on-one interviews; Nvivo software was employed to store, organize, and code the data, and data analysis utilized analytic induction and constant comparison techniques. Five themes emerged regarding edTPA preparation of these participants: (a) a lack of teacher training and resources, (b) receipt of informal information from teacher candidates (TCs), (c) perceptions of providing inadequate support, (d) CT experience with obtaining parental waivers and class recordings, and (e) a perceived edTPA tradeoff of increased stress for teacher development. There was a clear need in this district to: (a) better promote edTPA training opportunities, (b) consider compulsory edTPA training for CTs who supervised TCs, (c) share edTPA training handouts and resources with CTs, and (d) ensure that university faculty clearly communicate edTPA requirements to CTs.